Pluralities without reified Wholes : a phenomenological response to Hans Berhard Schmid’s collectivism - Chelstrom, Eric (Investigaciones Fenomenológicas, 2011)
Collective intentions form the basis of the social world and represent amode of experience overlooked in some phenomenological analysis: weintentionality.Some argue that the subject of intentionality is the intendingsubject, but phenomenology is committed to intentionality in essence beingsomething restricted to individual subjectivities.The intending subject, the conscious subject, is not equivalent to thesubject of intention or subject matter of acts of consciousness, i. e. it is notthe syntactical subject referenced in and through an intentional act. HansBernhard Schmid disagrees; here I present the case for subjective individualismwith respect to collective intentionality and respond to his argumentsfor collectivism.